Obstipace u dětí - Janásová, Petra (Sestra (Praha), 2008)
Up to 15 % of children suffer from constipation which can be a problem for the whole family. Even infants can have problems with elimination. Breast fed baby sometimes does not have a bowel movement for a week or two and then he has a large amount of soft stool of the color of scrambled eggs. It this case it is not constipation.
Keywords: Medical History Taking; Child; anamnéza; lidé; Constipation; dítě; zácpa; defekace; Defecation; Humans